Digitalisasi Agribisnis dan Social-Entrepreneurship Jamur Crispy Berbasis IoT melalui MycoGrow untuk Penguatan Usaha Kelompok Tani Nagari Taram - Anip Febtriko; Yandri; Tri Rahayuningsih Shasha (Jurnal Pengabdian Masyarakat - PIMAS, 2026)
The Oyster Mushroom Farmer Group in Nagari Taram, Harau District, Lima Puluh Kota Regency, has significant potential for developing oyster mushroom cultivation as a high-value agricultural commodity. However, cultivation practices and business management are still carried out using conventional methods, particularly in monitoring the temperature and humidity of mushroom growing houses, recording production data, and marketing products, which remains limited to local markets. These conditions have resulted in unstable production, a high baglog failure rate, low operational efficiency, and suboptimal business competitiveness. This community engagement program aims to enhance productivity and strengthen the farmer group's business through MycoGrow, an Internet of Things (IoT)-based digital cultivation and agribusiness model for oyster mushrooms. The proposed solutions include implementing a real-time environmental monitoring system using IoT sensors, digitalizing production records and business management through a dedicated application, and strengthening digital marketing via social media, online marketplaces, and product branding strategies. The implementation method consists of partner needs assessment, program socialization, technical training, technology deployment, mentoring, monitoring, evaluation, and the development of a sustainability strategy. The expected outcomes include improved cultivation stability and productivity, reduced baglog failure rates, comprehensive digitalization of business records, enhanced capacity of farmer group members in data-driven business management, and expanded market reach through digital platforms.